Lack of birth certificate and violation of human rights (2017)
Introduction: at present, in the territory of the United Mexican States, there is an imprecise number of human beings whose birth has never been recorded, which leads to several negative consequences for the exercise of their rights and has an effect on three different dimensions: A factual dimension, as the State denies services such as access to healthcare, administration of justice by courts, or participation in social security and education programs; an axiological dimension, since the human being is materially excluded from society, depriving them of the legal security that covers those who can identify themselves; and, lastly, a regulatorydimension, when individuals are denied recognition by the State. Methodology: the research problem is approached from the legal realism method, based on the analysis of phenomena that are present in object of study and its explanation, in relation to the sociological, economic, and legal consequences. Results: according to the figures presented, it is estimated that in our country there are around 10 million human beings whose birth has never been recorded, so they do not have access to healthcare, education, justice, recreation and free comprehensive development. Conclusions: the protection of human rights is seriously compromised by the lack of a birth certificate. In this sense, individuals are materially inexistent to the State and are denied the exercise of rights essential to live a decent life.